A Novel Training Program to Improve Human Spatial Orientation: Preliminary Findings - McLaren-Gradinaru, Michael; Burles, Ford; Dhillon, Inderpreet; Leonidas David, Adam; Umiltà, Alberto; Hannah, Jaimy; Dolhan, Kira; Iaria, Giuseppe (Frontiers in Human Neuroscience, 2020)
The ability to form a mental representation of the surrounding is a critical skill for spatial navigation and orientation in humans. Such a mental representation is known as “cognitive map” and is formed as individuals familiarize themselves with the surrounding, providing detailed information about salient environmental landmarks and their spatial relationships. Cognitive maps are critical to successful orientation since, once formed, they allow individuals to reach any target location from anywhere within the environment, and even permit generating alternative, unexplored routes if required by environmental circumstances. The inability to effectively form cognitive maps is typically compensated by the use of less efficient approaches to navigation such as memorizing a series of turns and distances, which leads to struggles with navigating large-scale environments, making dayly life activities more challenging. To date, despite the evidence on the malleability and potential training of general spatial orientation skills in humans, it remains unknown whether or not the specific ability to form cognitive maps cab be improved by an appositely developed training program. Here, we examined the potential to train the ability to form cognitive maps by using a computerized program in a virtual environment designed appositely to simulate the acquisition of this important skill. Fifteen healthy adults completed a 12-day training and were administered a comprehensive spatial behavioural assessment before and after the training program. The results showed that the training program significantly improved the participants’ ability to form cognitive maps. The training program did not significantly improve more specific cognitive functions such as mental rotation and perspective-taking, suggesting that the program targets specifically the higher-level cognitive ability to form a mental representation of the surrounding. These preliminary findings provide the very first evidence that the human ability to form a cognitive map for orientation and navigation is a trainable skill. This could have a significant positive impact in the lives of many individuals affected by topographical disorientation as a result of an acquired or developmental condition, or individuals undergoing a cognitive decline as in the aging population.